POLICY FORMULATION FOR VILLAGE REGULATION PLAN REGARDING DIGITAL SERVICES IN CIJULANG VILLAGE PANGANDARAN REGENCY - Dinia Anis Setiani; Rizky Ilhami (SEAN Institute, 2023)
Plan regarding Digital Services in Cijulang Village, Pangandaran Regency and describe the formulation of policies that will be taken and determined to become legal policy. In this study, the authors examine the Policy Formulation of Village Regulation Plans Regarding Digital Services in Cijulang Village, Pangandaran Regency using the dimensions of problem formulation, policy agenda, selection of alternative policy problem formulations and stages of policy establishment. This study used a qualitative method with a descriptive approach. The data obtained in this study were sourced from observation, interviews and documentation and selected 2 (two) informants as people who were believed to be able to provide the correct data and information, including; Head of Cijulang Village and the Head of General Affairs for Cijulang Village. Based on the research results that the author has obtained, the Policy Formulation of the Village Regulation Plan Regarding Digital Services in Cijulang Village, Pangandaran Regency, has not gone well because the policy of the planned village regulations regarding digital services has not yet been discussed in depth and has not even made regulations regarding this matter. For this reason, the government of Cijulang Village will take these policy steps as soon as possible and include them in the Village Government Work Plan because currently, Cijulang Village is still carrying out various non-digital services.